2008
DOI: 10.2140/gtm.2008.13.41
|View full text |Cite
|
Sign up to set email alerts
|

A family of embedding spaces

Abstract: Let Emb(S^j,S^n) denote the space of C^infty-smooth embeddings of the j-sphere in the n-sphere. This paper considers homotopy-theoretic properties of the family of spaces Emb(S^j,S^n) for n >= j > 0. There is a homotopy-equivalence of Emb(S^j,S^n) with SO_{n+1} times_{SO_{n-j}} K_{n,j} where K_{n,j} is the space of embeddings of R^j in R^n which are standard outside of a ball. The main results of this paper are that K_{n,j} is (2n-3j-4)-connected, the computation of pi_{2n-3j-3} (K_{n,j}) together with a geome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
121
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(121 citation statements)
references
References 76 publications
(124 reference statements)
0
121
0
Order By: Relevance
“…and their generators. Recently, Budney [4] has given a description of such Haefliger knots in terms of the space of long knots, which is related to the Litherland-type deform-spinning.…”
Section: Haefliger's Knotsmentioning
confidence: 99%
See 2 more Smart Citations
“…and their generators. Recently, Budney [4] has given a description of such Haefliger knots in terms of the space of long knots, which is related to the Litherland-type deform-spinning.…”
Section: Haefliger's Knotsmentioning
confidence: 99%
“…‫ޒ‬ n being the standard inclusions on jxj 1 for x 2 ‫ޒ‬ j . Then, Budney [4], using results of Goodwillie [9], showed that there is an isomorphism 2 K 4;1 ! C …”
Section: Haefliger's Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeeman proved that the complements of co-dimension two -twistspun knots fibre over 1 provided ∕ = 0 [8]. Litherland [7] went on to formulate a general situation where a deform-spun knot complements fibre over 1 . Specifically, Litherland proved that if the diffeomorphism :…”
mentioning
confidence: 99%
“…In the paper [1] the first author gave a new proof of Haefliger's theorem, where the monoid of isotopy classes of smooth embeddings of in is a group, provided − > 2. The heart of the proof is showing that if − > 2, then every knot ( , ) (where…”
mentioning
confidence: 99%